Thermohydraulic Analysis of Ocean Thermal Energy Conversion - Andi Hendrawan; Aji K. Hendrawan; Sri Pramomo; Lusiani Lusiani (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
Thermohydraulic analysis is a mandatory analysis for power plants, including in this case marine thermal power plants (OTEC = ocens thermal energy conversion). The application to OTEC shows that temperature and pressure are things that must be considered, the higher the surface temperature, the greater the output power. Calculation of heat flow is a variable that is determined before a plant is built. This study aims to make a mathematical analysis of heat flow or thermohydraulic. The study uses the study of the heritage of Mendalan so that modeling and determination of design variables are formed, including heat flow in the pipe, diameter, hot and cold water discharge and boiler variables